The Protective Effect of the Soluble Egg Antigen of Schistosoma japonicum in A Mouse Skin Transplantation Model - Jiang, Jie; Li, Junhui; Zhang, Yu; Zhou, Chen; Guo, Chen; Zhou, Zhaoqin; Ming, Yingzi (Frontiers in Immunology, 2022)
Background: Organ transplantation is currently an effective method for treating organ failure. Long-term use of immunosuppressive drugs has huge side effects, which severely restricts the long-term survival of patients. Schistosoma can affect the host's immune system by synthesizing, secreting, or excreting a variety of immunomodulatory molecules, but its role in transplantation was not well defined. In order to explore whether Schistosoma-related products can suppress rejection and induce long-term survival of the transplant, we used soluble egg antigen (SEA) of Schistosoma japonicum in mouse skin transplantation models. Material and methods: Each mouse was intraperitoneally injected with 100ug SEA three times a week for four consecutive weeks before allogenic skin transplant. Skin transplants were performed on day 0 and then to observe graft survival. Skin grafts received pathological examination 7days post transplantation. And the skin grafts were subjected to mRNA sequencing. Bioinformatics analysis was conducted and the expression of part hub genes was verified by qPCR. Flow cytometry analysis was performed to evaluate the immune status and validate the results from bioinformatic analysis. Results: The mean survival time (MST) of mouse skin grafts in the SEA-treated group was 11.67±0.69 days, while that of the control group was 8.00±0.36 days. Pathological analysis showed that Sj SEA treatment led to reduced inflammatory infiltration within skin grafts 7 days after allogenic skin transplantation. Bioinformatics analysis identified 86 DEGs between Sj SEA treatment group and control group, including 39 up-regulated genes and 47 down-regulated genes. Further analysis revealed that Sj SEA mediated regulation on cellular response to interferon−γ, activation of IL−17 signaling and chemokine signaling pathways, as well as cytokine-cytokine receptor interaction. Flow cytometry analysis showed SEA treatment led to higher percentages of CD4+IL-4+T cells and CD4+Foxp3+T cells and decreased CD4+IFN-γ+T cells in skin transplantation. Conclusion: Sj SEA treatment suppressed rejection and prolonged skin grafts survival by regulating immune responses. Sj SEA treatment might be a potential new therapeutic strategy to facilitate anti-rejection therapy and even to induce tolerance.